Flipped Classroom dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan: Implementasi, Manfaat, dan Tantangan - Julham Hukom (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
This study examines the application of the Flipped Classroom model in Pancasila and Civic Education (PPKn/Pendidikan Pancasila) learning through a systematic literature review. The conventional teacher-centered approach in PPKn often fails to develop students' critical thinking and civic values optimally. The Flipped Classroom model, where students learn material independently at home through digital media before class, and use classroom time for active discussions and collaborative tasks, offers a promising alternative. Based on the review of 15 relevant studies published between 2017 and 2024, this article analyzes: (1) the conceptual foundation of the Flipped Classroom model; (2) its implementation stages in PPKn learning; (3) the benefits it brings to student learning outcomes and character development; and (4) challenges encountered during implementation. The findings indicate that the Flipped Classroom model significantly increases student learning activity, critical thinking skills, and understanding of Pancasila values. Key implementation challenges include limited student access to digital technology, insufficient teacher digital competency, and the need for consistent student self-discipline. The article concludes with practical recommendations for PPKn educators to adopt this model effectively in the era of the Merdeka Curriculum.